The Seddling Growth of Nyatoh (Palaquium spp.) on PT. Antam’s Tailing Media Business Unit of Pongkor in Addition of Coconat Shell Charcoal and Bokashi Compost - Basuki Wasis; Hafiizh Baskara (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Sludge of gold mining is one of main toxic sludge toward environment because level of high acidity, so that can damage soil fertility and local vegetation as impact from toxicity and contaminant of food chain. That characteristic of tailing can cause problems in revegetation activity, so needing an effort for land repairing with adding coconut shell charcoal and bokashi compost fertilizer before a revegetation effort. Cococnut shell charcoal and bokashi compost fertilizer can repair soil condition that is poor of nutrients as a nutrient source and microbe for soil fertility. Beside that, an effort that need to be conducted is selection of appropiate plant species. Nyatoh (Palaquium spp) is one of local plant in Indonesia that can be recomended to be devoleped in revegetation effort at ex-mine area.